Development, Modernization, and Son Preference in Fertility Decisions - Filmer, Deon; Friedman, Jed; Schady, Norbert (World Bank, Washington, DC, 2012)
A family preference for sons over daughters may manifest itself in different ways, including higher mortality, worse health status, or lower educational attainment among girls. This study focuses on one measure of son preference in the developing world, namely the likelihood of continued childbearing given the gender composition of existing children in the family. The authors use an unusually large data set, covering 65 countries and approximately 5 million births. The analysis shows that son preference is apparent in many regions of the developing world and is particularly large in South Asia and in the Eastern Europe and Central Asia region. Modernization does not appear to reduce son preference. For example, in South Asia son preference is larger for women with more education and is increasing over time. The explanation for these patterns appears to be that latent son preference in childbearing is more likely to manifest itself when fertility levels are low. As a result of son preference, girls tend to grow up with significantly more siblings than boys do, which may have implications for their wellbeing if there are quantity-quality trade-offs that result in fewer material and emotional resources allocated to children in larger families.